Transsutural Distraction and Tissue Regeneration of the Midfacial Skeleton: Experimental Studies in Growing Dogs. (May 2014) - Yusheng, Yao; Chengyue, Wang; Zhiying, Wang; Guijun, Wang
Objective: The purpose of this study was to evaluate the effect of different mechanical forces on the expansion of the palatine suture using transsutural distraction osteogenesis. Methods: A total of 48 dogs were used in this study. The experimental groups were treated with a custom-designed internal distractor. Bone regeneration was determined with x-rays and histology. The computed values underwent statistical analyses using analysis of variance. Results: The maxillary complex was most noticeably advanced with an applied mechanical force of 600 g (20.15 ± 1.36 mm), compared with forces of 400 g (19.88 ± 1.41 mm) and 800 g (2.24 ± 0.93 mm). Immunohistochemical staining showed that the expression of bone morphogenetic protein-2 and bone morphogenetic protein-4 fluctuated with different mechanical forces. These changes were statistically significant when 600 g of force was applied within 30 days of distraction ( P < .05). Conclusions: Transsutural distraction osteogenesis in the growing dog should be safe and well tolerated in inducing bony lengthening of the maxilla, and the optimal force is 600 × g. Bone morphogenetic protein-2 and bone morphogenetic protein-4 may play an important roles in the signaling pathways that link mechanical forces and biological responses.